Hubungan Kecerdasan Emosional Dengan Strategi Coping Pada Mahasiswa Program Studi Pendidikan Dokter (PSPD) Fakultas Kedokteran Universitas Lampung - Serra Meilawati; Denny Andika Kurniawan; Dwita Oktaria; Merry Indah Sari (CV. Jasa Sukses Abadi, 2023)
The stress level of medical students is very high when compared to other study programs in the non-medical sector with academic-related problems being the stressor main. Medium stress level is the stress level most experienced by students of the Faculty of Medicine, University of Lampung. Stress can have negative effects such as difficulty concentrating and health problems. It is important to develop coping strategies in dealing with stress so that negative impacts do not arise. Efforts or reactions that arise when individuals face stress are called coping strategies. The choice of coping strategies can be influenced by various factors, one of which is emotional intelligence. The ability to recognize and manage emotions that are felt by oneself and others is called emotional intelligence. High emotional intelligence possessed by an individual will make the individual considered able to solve the problem well. The purpose of this study was to determine the relationship between emotional intelligence and coping strategies in students of the Medical Education Study Program (PSPD), Faculty of Medicine, University of Lampung. The data in this study were collected using emotional intelligence questionnaires and coping strategies that had been tested for validity and reliability. The stratified random sampling technique was used in taking 255 samples of the PSPD FK Unila students class of 2017, 2018, 2019, and 2020. Univariate analysis showed that the level of emotional intelligence most respondents had was 76% high emotional intelligence, 24% medium emotional intelligence, and no low emotional intelligence. Respondents who chose problem focused coping 96% and emotional focused coping 4%. Bivariate analysis with Fisher Exact test obtained p <0.05, so the conclusion is that there is a relationship between emotional intelligence and coping strategies in students of the Medical Education Study Program (PSPD), Faculty of Medicine, University of Lampung.